(untitled) (Fiep Bulletin - online, 2019)
The present study had as objective to verify the prevalence of behaviors indicative of eating disorders inadolescents of the final series of Elementary School, making a comparison between the concern with the corporal image and possiblebehaviors that could indicate indications of risk eating habits through BMI - Body Mass Index, BSQ Body Image Questionnaire, andEAT-26 Food Attitudes Questionnaire, to evaluate body image, and possible symptoms of anorexia nervosa. In the results obtained, itwas observed that for n = 66, 21 students (31.8%) were underweight, 32 students (48.5%) had the ideal weight, 9 students (13.6% %)are overweight, 2 students (3%) have Obesity grade I, and 2 students (3%) have Obesity grade II. It was also observed that, amongthe students evaluated (n = 66), no student presented a high risk of developing an eating disorder, 16 students (24.2%) presented lowrisk, and 50 students (75.8%) did not present risk. As to body image distortion, 39 (59.1%) were within normal range, 7 (10.6%)presented mild distortion, 8 (12.1%) presented moderate distortion and 12 (18 , 2%) present severe distortion of body image.